Aplikasi Bahan Organik pada Tanaman Sorgum (Sorghum bicolor L.Moench) var. KD4 di Lahan Kering untuk Peningkatan Penyediaan Hara - Suminarti, N.E.; A.Y. Guntoro; A. N. Fajrin (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Suminarti et al, 2018. Application of Organic Matter in Sorghum Plants (Sorghum bicolor L.Moench) var. KD4 on Dry Lands for Soil Nutrient Supply Improvement. JLSO 7(2):144-156. The low content of soil organic matter and soil fertility are characteristics of dry land. Therefore, so the land can be utilized for agricultural farming, a material that is capable of acting as a soil improvement is needed, namely organic matter. The study aimed to examine the effect of the source and dosage of organic matter on the supply of nutrients, growth and yield of sorghum plants was carried out in July 2016 in the experimental garden of Brawijaya University. A split plot design was used in this study. The sources of organic material (sugar can waste, organic waste compost and cow dung) were set as the main plot, whereas doses of organic matter (125, 100 and 75) % of recommended dosage as subplots. The study was repeated 3 times. Soil analysis was carried out 3 times, namely: (1) before planting (BO, N content, P, K soil, soil pH and soil texture), (2) after application of organic material (BO and N, P, K soil content) and (3) after harvest (BO and N, P, K soil content). The agronomic observations were carried out destructively on generative phase at 80 days after planting (DAP) including the components of growth (root dry weight, leaf area, and total dry weight of the plant) and harvest at age of 90 DAP. F test at 5% level was used to test the effect of treatment, while the difference between treatments was based on LSD level of 5%. The results showed that there was a significant interaction between the source and dosage of organic matter on the variable leaf area and total dry weight. The highest yield was obtained in sugar can waste at various doses. Higher yields of seeds per hectare were also found in sugar can waste which is equal to 1.76 tons ha-1. The sugar can waste application is able to provide N, P and K soil elements of 18.3%, 85.68% and 8.42% respectively compared to organic waste compost and cow dung.